Вычислить Под общим корнем 6+2√5 - под общим корнем 6-2√5

Вычислить Под общим корнем 6+2√5 - под общим корнем 6-2√5
Гость
Ответ(ы) на вопрос:
Гость
[latex] \sqrt{6+2 \sqrt 5} - \sqrt{6-2 \sqrt 5} =\sqrt{({1+\sqrt5})^2}-\sqrt{({1-\sqrt5})^2}=|1+\sqrt5|- \\ -|1-\sqrt5|=(1+\sqrt5)-(\sqrt5-1)=2[/latex]
Гость
[latex] \sqrt{6+2 \sqrt{5} } - \sqrt{6-2 \sqrt{5} } = \sqrt{( \sqrt{5})^{2}+2 \sqrt{5}+1^{2} } - \sqrt{( \sqrt{5})^{2}-2 \sqrt{5}+1^{2} }= \\ [/latex] [latex] \sqrt{( \sqrt{5}+1)^{2 } }- \sqrt{( \sqrt{5}-1)^{2 } }=| \sqrt{5}+1|-| \sqrt{5}-1| = \sqrt{5}+1- \sqrt{5}+1= \\ =2 \\ [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы